Pengembangan Strategi Pemasaran Dengan Rebranding Tkl Ecopark : Pendekatan Marketing Mix - Sih Bagas Pangerando; Ivo Novitaningtyas (Jurnal Ilmiah Manajemen Bisnis dan Ekonomi Kreatif, 2023)
This research in order to identify the development of marketing strategic take place in the kyai langgeng park in approach with marketing mix. This development will analyze using SWOT analysis. SWOT analysis is used to known the internal factor based on mix marketing and the external factor based on the circumstance factor, economic factor, socio-cultural factor, political factor, and technology. The result of the SWOT analysis shown the Kyai Langgeng park ha e several strong sector and another weak sector and another threat based on the analysis and have to take the action immediatelly. Based on the SWOT analysis Kyai Langgeng park needs to do something special especiallay the newest rebarnd or transform the whole system and organization. There are three transformation need to do by Kyai langgeng park the first one is business model transmation, brand image transformation, and financially transformation.